PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) UNTUK HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 005 KOTA MEDANKECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Eliza, Eliza; Alim, Jesi Alexander; Alpusahri, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aim to for result of learning class student mathematics of III SD Negeri 005 Kota Medanacademic year 2014 / 2015. Subjek in this research class student of III SD Negeri 005 Kota Medan with amount of student counted 28 students. Form this research of action class which collaborative with two study cycle. This data research of that result learn natural student improvement, activity provision value learn first cycle with average 45,5 %, 63,4 %. This second cycle mount with average 72,7%, 81,8%. Student activity first cycle with average 55,5 %, 66,6 % and second cycle mount with average 77,8 %, 88,9 %. This result of natural research improvement, where before conducted action applying of study of mathematics of realistik Indonesia (PMRI) complete elementary score 7 student ( 25 %) with average ( 62,32 %). Second cycle mount with is complete people ( 19) with average 72,32 . The second cycle mount with complete reach people ( 25) with average 83,21 %. Thereby can be concluded that hypothesis in this research " if applied education of mathematics of realistik Indonesia ( PMRI) hence can improve result learn class student mathematics of III SD Negeri 005 Kota Medan district of Kelayang Subprovince of Indragiri Hulu " can be accepted.Keyword : Education of Mathematics Realistik Indonesia (PMRI), Result Learn Mathematics